2016
DOI: 10.1371/journal.pone.0167829
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Dispersal by Birds in a Dynamic Urban Ecosystem

Abstract: Changes in land cover during urbanization profoundly affect the diversity of bird communities, but the demographic mechanisms affecting diversity are poorly known. We advance such understanding by documenting how urbanization influences breeding dispersal—the annual movement of territorial adults—of six songbird species in the Seattle, WA, USA metropolitan area. We color-banded adults and mapped the centers of their annual breeding activities from 2000–2010 to obtain 504 consecutive movements by 337 adults. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 70 publications
0
12
0
2
Order By: Relevance
“…Studies that documented land change over time and related it to changes in ecological processes would be especially useful. A motivating example is provided by Marzluff, DeLap, Oleyar, Whittaker, and Gardner (), who studied avian dispersal as a function of land change within breeding territories by quantifying the area converted from forest to built land each year (see Moll et al., for additional examples of dynamic metrics). We recommend that future studies consider how to weave dynamic land‐use effects into urban ecological research, given its clear relevance and strongly overlooked nature (Pickett et al., ; Ramalho & Hobbs, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that documented land change over time and related it to changes in ecological processes would be especially useful. A motivating example is provided by Marzluff, DeLap, Oleyar, Whittaker, and Gardner (), who studied avian dispersal as a function of land change within breeding territories by quantifying the area converted from forest to built land each year (see Moll et al., for additional examples of dynamic metrics). We recommend that future studies consider how to weave dynamic land‐use effects into urban ecological research, given its clear relevance and strongly overlooked nature (Pickett et al., ; Ramalho & Hobbs, ).…”
Section: Discussionmentioning
confidence: 99%
“…The intra-patch flights of up to 200m were neither confined to contiguous habitat nor, in all cases, reliant upon these corridors. This is perhaps surprising given that previous studies found that birds were (i) reluctant to leave sites when separated by urban development [55], (ii) incurred apparent survival/productivity costs when switching patches [56], (iii) gap-crossing tendency is apparently allometric [57] and (iv) that insectivores, in particular, were unlikely to penetrate edges [58]. Our findings do not corroborate the idea that energetic cost and vulnerability to predation (from aerial predators) means that small songbirds are unlikely to undertake edge crossing behaviour [16,17,59].…”
Section: Discussionmentioning
confidence: 93%
“…Field studies invariably rely on methodologically limited movement data for the questions addressed in our study, i.e. point counts, citizen science monitoring programs, proximity loggers or colour ring resightings [18,55,56,63]. However, while they provide complementary insights into processes of species abundance and assemblage, below the population level, the individual is rarely considered [4,9,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…The creation of new green space in urban landscapes increases the amount of habitat available to birds. While such green space can also expose birds to increased anthropogenic threats [ 141 , 142 ], these threats are often offset by the benefits of additional habitat which supports bird populations [ 31 , 79 , 143 ]. Consequently, creating urban green space remains important for bird conservation [ 120 , 144 ].…”
Section: Discussionmentioning
confidence: 99%